HTC255: Catering System and Management / Faculty of Hotel & Tourism Management - UiTM, Faculty of Hotel and Tourism Management (2023)
The basic idea of System Theory is that organizations have common characteristics with all other living systems. A thorough understanding of these characteristics allows us to work with the natural tendencies rather than against them unnecessarily. Hence, the course provides for a critical analysis of the foodservice management from a system approach perspective. Students are exposed to the systems approach of foodservice management in order to provide for a sound management capability.